Space and time in the architecture of Prehistoric enclosures. The Iberian Peninsula as a case study. - Márquez-Romero, José Enrique; Jiménez-Jáimez, Víctor José (Routledge, 2014)
Space and Time in Mediterranean Prehistory addresses these two concepts as interrelated, rather than as separate categories, and as a means for understanding past social relations at different scales. The need for this volume was realised through four main observations: the ever growing interest in space and spatiality across the social sciences; the comparative theoretical and methodological neglect of time and temporality; the lack in the existing literature of an explicit and balanced focus on both space and time; and the large amount of new information coming from prehistoric Mediterranean. It focuses on the active and interactive role of space and time in the production of any social environment, drawing equally on contemporary theory and on case-studies from Mediterranean prehistory. Space and Time in Mediterranean Prehistory seeks to break down the space-time continuum, often assumed rather than inferred, into space-time units and to uncover the varying and variable interrelations of space and time in prehistoric societies across the Mediterranean. The volume is a response to the dissatisfaction with traditional views of space and time in prehistory and revisits these concepts to develop a timely integrative conceptual and analytical framework for the study of space and time in archaeology.
Política de acceso abierto tomada de: https://www.routledge.com/our-products/open-access-books/publishing-oa-books/chapters#
Keywords: Península Ibérica - Historia - Epoca prehistórica; Restos arqueológicos prehistóricos; Abandono ritual; Recintos de fosos; Neolítico; Península ibérica; Calcolítico